Energy storage evaluation under surge load in an off-grid photovoltaic system - Wong, Li Mei (2022)
This study analyses the performances battery energy storages under surge load condition in an off-grid photovoltaic (PV) system whereby the surge load condition refers to the high start-up current being drawn by the motor load. The main contribution of this paper is determining the performances in terms of voltage, current and state-of-charge of the three energy storages: lead acid battery, lithium-ion battery, and supercapacitor under surge load condition when connected to an off-grid PV system. The modelling circuit consists of a solar PV array, maximum power point tracking charge controller, energy storage, DC-DC converter, inverter and AC load and the circuit is constructed based on the previous literatures regarding off-grid PV system. This is achieved by modelling the off-grid PV system using MATLAB/Simulink software and the surge load is modelled by using single-phase induction motor which is available in Simulink Simscape library. Important parameters data are retrieved from the available journals to be applied in the Simulink simulation. The performance of the battery energy storage is then evaluated and compared among each other.